COVID-19 messenger ribonucleic acid vaccination and abnormal radiopharmaceutical uptake in the axilla visualized on 68Ga-DOTATATE positron-emission tomography/computed tomography - Weissman, Joshua; Bartel, Twyla (World Journal of Nuclear Medicine, 2021)
As COVID-19 vaccination rates continue to rise, it is becoming increasingly important to understand diagnostic imaging associations' resultant from the vaccines. Here, we report a case of a 59-year-old female who was in remission for gastrointestinal neuroendocrine carcinoma and presented for standard follow-up imaging evaluation. Positron-emission tomography (PET) images from a 68Ga-DOTATATE PET (NETSPOT) demonstrated moderate focal radiotracer uptake in the right axilla. Interestingly, this uptake localized to several normal-sized lymph nodes on the corresponding computed tomography (CT). A medical history revealed the patient received both doses of an ipsilateral COVID-19 messenger ribonucleic acid vaccine injection at 17 and 38 days before the PET/CT study. Subsequent scans 2 months later revealed no radiotracer uptake.
Keywords: 68Ga-DOTATATE; COVID-19; NETSPOT; positron-emission tomography; vaccination